Biochemical aspects of mammalian melanocytes and the emerging role of melanocyte stem cells in dermatological therapies - Ali, Sharique A.; Naaz, Ishrat (International Journal of Health Sciences, 2018)
Skin color in animals is richer than human beings and is determined by different types of pigments. Melanin is the key pigment responsible for the diverse pigmentation found in animal and human skin, hair and eyes. Melanin pigment is synthesized by melanocytes and is consecutively transferred to adjacent keratinocytes; here it acts as an internal sunscreen to defend from ultraviolet (UV) damage. Any defect in the process of melanocytes development and/or melanin synthesis results in aesthetic problem of abnormal pigmentation. Clinically, abnormal pigmentation displays distinct increased or reduced pigment levels, known as hyperpigmentation or hypopigmentation. These defects affect either the melanocyte number or its function. Herein we discuss the fundamental aspects of melanocytes/melanin biology taken together the underlying cause of pigmentary disorders. The current chapter also gives an insight into the melanocyte stem cells (MSCs) biology, which in turn can facilitate the development of novel treatment regimens for dermatological disorders.